A gargoyle's guide to murder - Pandian, Gigi, 1975- (Pandian, Gigi, 1975- Accidental alchemist, 2025)
"Dorian Robert-Houdin is used to living his life in the shadows, his existence only known to a few trusted friends. When a dangerous book from his past resurfaces, he follows his closest confidante, alchemist Zoe Faust, from Oregon to England to investigate. Before he can examine the magical book, Dorian witnesses a murder amidst the foggy lanes of Oxford. But when he takes Zoe to the scene there's no body -- and no evidence a crime has taken place. Using his unique skills as a gargoyle, Dorian sets out to solve the baffling crime nobody else believes occurred. When Dorian and Zoe discover a dead man in a bookshop filled with arsenic-laced books, the victim isn't a stranger -- he's connected to the vanishing crime scene. The trail leads to a country house party where a group of bibliophile suspects have gathered and a storm is brewing. Could the killer be the mercurial Agatha Christie scholar? The prickly literature professor? The secretive rare books expert? With an unscrupulous book thief lurking, can sleuths Dorian and Zoe unmask a murderer before the next page brings them to a perilous end?"--